Гостинність – традиційні форми спілкування в минулому і сьогоденні - Вражиновський, Т. (Народна творчість та етнографія, 2009)
Hospitality is an interesting and important universal problem in many aspects and on different levels of its manifestation, primarily in common law. It is an important element of daily ceremonial practice. The role of a guest and respective ritual procedures has especial importance in the study of hospitality. In common law a guest is tattooed and may not be aggrieved; certain theologization of a guest is visible in the past and even present practices. In the folk culture arrival of a guest is cohered with appearance of a deity or one of the deceased ancestors. The subject of the analysis presented in our article is typical forms of interaction between Macedonians on the levels: guest – rural environment and guest – family during arrival and greetings, on the level of unknown, unbidden – and known or accepted, related to different situations: daily visits, high-day visits etc. First of all we pay attention to some norms in the interaction: a) news about the arrival of a guest; b) forms of communication during the meeting of a guest; c) place of a guest in the visited house and how hosts treat him/her; d) ways to see off a guest; e) how a rural community treats those who come to their village – aliens. These forms of interactions determine interpersonal relationships and notion of respect, which defines attitude to a person in general. They represent modes to regulate interpersonal communication within rural environment, and on a smaller scale within a family.